Information management model for customer complaints in residential building companies - Bazzan, Jordana (2024)
The warranty service department of residential building companies must provide effective repair services during the defect liability period and feedback for the quality system by collecting and processing data on building defects. These data can be used as a knowledge source to improve the quality of new design and production processes. However, effective complaint data management has been challenging for this sector, as complaint records often do not have enough information to fully identify the cause of defects. Previous studies on customer complaints are mostly related to generating metrics based on existing databases but fail to explain how to effectively perform data collection and processing. This study aims to devise an information management model for customer complaints in the real estate market to support quality improvements and warranty service. Using Design Science Research as the methodological approach, this study is being held in partnership with a large Brazilian Residential Building Company. Interviews, data analysis, and data collection during warranty services were carried out during this investigation The proposed model includes a complete and detailed data collection as well as the preposition of product and service quality indicators. Technologies such as Natural Language Processing and Machine Learning were used to improve the data collection and introduce some degree of automation during the reception of customer complaints phase. Regarding the inspection and repair stages, protocols to collect and analyze complaint data were proposed using causal-effect analysis, especially focusing on product quality. Additionally, the proposed model includes indicators on the quality of warranty services and a repair time forecast tool to estimate the service time during the inspection. The artifact's purpose is to guide residential building companies in devising information systems for managing customer complaint data to improve product and service quality. Consequently, the model will enable companies to understand the occurrence of building defects and to implement improvement actions in future projects. This investigation also changes the traditional approach of simply providing repair to offer a specialized service focused on the customer’s experience